Determination of the hydrogen-bond network and the ferrimagnetic structure of a rockbridgeite-type compound, Fe2+Fe3.23+(Mn2+, Zn)0.8(PO4)3(OH)4.2(HOH)0.8. (17th May 2018) - Röska, B; Park, S-H; Behal, D; Hess, K-U; Günther, A; Benka, G; Pfleiderer, C; Hoelzel, M; Kimura, T
Abstract: Applying neutron powder diffraction, four unique hydrogen positions were determined in a rockbridgeite-type compound, . Its honeycomb-like H-bond network running without interruption along the crystallographic axis resembles those in alkali sulphatic and arsenatic oxyhydroxides. They provide the so-called dynamically disordered H-bond network over which protons are superconducting in a vehicle mechanism. This is indicated by dramatic increases of dielectric constant and loss factor at room temperature. The relevance of static and dynamic disorder of OH and HOH groups are explained in terms of a high number of structural defects at octahedral chains alternatingly half-occupied by cations. The structure is built up by unusual octahedral doublet, triplet, and quartet clusters of aliovalent 3 d transition metal cations, predicting complicate magnetic ordering and interaction. The ferrimagnetic structure below the Curie temperature –83 K could be determined from the structure analysis with neutron diffraction data at 25 K.